Impact of raw ham quality and tumbling time on the technological properties of polyphosphate-free cooked ham. (June 2020) - Steen, Liselot; Neyrinck, Ellen; De Mey, Eveline; De Grande, Annatachja; Telleir, Danny; Raes, Katleen; Paelinck, Hubert; Fraeye, Ilse
Abstract: The effect of tumbling time (5 h30, 19 h and 26 h) and raw ham quality (superior, inferior or mixed quality) on the quality of polyphosphate-free cooked ham was investigated. The water holding capacity and total yield of the polyphosphate-free tumbled hams were dependent on both tumbling time and ham quality. Higher values of both parameters were obtained with an increase in tumbling time from 5 h30 to 19 h and with superior hams. The exudate after 19 h and 26 h tumbling showed a higher gel forming ability compared to 5 h30, which, in case of polyphosphate-free cooked hams produced with mixed and inferior meat quality, resulted in a better sliceability (less holes). However, tumbling time did not affect hardness, which was only influenced by ham quality, resulting in a softer polyphosphate-free cooked ham produced with inferior ham quality compared to the other quality classes. Highlights: Water holding capacity (WHC) and total yield (TOY) were better for superior hams. Increase in tumbling time (5 h30 to 19 h) resulted in an increase in WHC and TOY. Better gel forming ability of exudate was obtained with increasing tumbling time. Longer tumbled (19 h and 26 h) inferior and mixed hams had a better sliceability. Hardness was only influenced by ham quality.